The implementation of information technology projects in Polish research and academic libraries in the early 1990 s. Questions of scope and effectiveness - Górny, Mirosław; Jazdon, Artur (My University, 1997)
Reports the results of an inquiry directed at Polish academic, research and scientific libraries. An appraisal of the current IT infrastructure, degree of advances in automation in libraries, and utilization of the electronic sources has been carried out, based on the completed questionnaires received from the libraries in question. It has been recognized that the best developed IT infrastructure is to be found in the academic libraries and that they are well prepared for automation. The situation is much worse in the special libraries of the research and scientific institutes. Half of the libraries in the latter group are not engaged in any preparation for automation, mainly owing to a lack of financial resources. Also, they do not provide readers with access to sources in an electronic format. Points out that a relevant consistent programme for the implementation and utilization of IT in Polish libraries has not yet been prepared.